Neuromuscular, biochemical and perceptual post-match fatigue in professional rugby league forwards and backs - Twist, C.; Waldron, M.; Highton, J.; Burt, D.; Daniels, M. (Journal of Sports Sciences, 2012)
In this study, we investigated changes in creatine kinase, perceptual and neuromuscular fatigue of professional rugby league players after match-play. Twenty-three male rugby league players (10 backs, 13 forwards) had their creatine kinase, perceptual ratings of fatigue, attitude to training, muscle soreness, and flight time in a countermovement jump measured before and 1 and 2 days after (day 1 and day 2 respectively) league matches. Total playing time, offensive and defensive contacts were also recorded for each player. Creatine kinase was higher both 1 and 2 days after than before matches (P < 0.05) in forwards and backs. Similarly, perceived fatigue and muscle soreness were higher than pre-match on both days 1 and 2 (P < 0.05), but did not differ between groups (P > 0.05). Jump performance was lower on day 1 but not day 2 for both groups (P < 0.05). While total playing time was longer in backs (P < 0.05), relative frequencies for all contacts were greater in forwards (P < 0.05). Contacts for forwards were correlated with all markers of fatigue (P < 0.05), but only flight time was correlated with offensive contacts in backs (P < 0.05). Despite the mechanisms of fatigue being different between forwards and backs, our results highlight the multidimensional nature of fatigue after a rugby league match and that these markers do not differ between positions.